High-strength waterproof concrete pole

By using a combination of waterproof coating and multi-arm star polymer defoaming agent in concrete poles, the problem of moisture invasion and corrosion of concrete poles in harsh environments is solved, high-strength waterproof and corrosion resistance are achieved, and the service life of the poles is extended.

CN119774953AActive Publication Date: 2025-04-08GUANGDONG FENGYE POWER EQUIP CO LTD

Patent Information

Application Number
CN202510064038.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Concrete electric poles are susceptible to corrosion problems caused by moisture in harsh environments, resulting in reduced structural performance and shortened service life.

Method used

The defoaming agent is used with waterproof coating and multi-arm star-shaped polymer as the main components, which plays a joint waterproofing role between the inside and the outside. The defoaming agent has good dispersion and defoaming properties, and can fill some micropores of concrete.

Benefits of technology

It significantly improves the waterproof performance and corrosion resistance of concrete poles, extends the service life of poles, and reduces maintenance workload.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774953A_ABST
    Figure CN119774953A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength waterproof concrete pole, and belongs to the technical field of concrete materials, the high-strength waterproof concrete pole comprises high-strength waterproof concrete, a reinforcement cage and a waterproof coating coated on the surface of the pole, the high-strength waterproof concrete comprises the following components in proportion: 750-850kg / m < 3 > of cement, 130-170kg / m < 3 > of silica fume, 1000-1300kg / m < 3 > of sand, 150-250kg / m < 3 > of steel fiber, 10-15kg / m < 3 > of water reducing agent, 170-190kg / m < 3 > of water and 0.5-1.5 kg / m < 3 > of defoaming agent; the waterproof coating and the defoaming agent with the multi-arm star-shaped polymer as the main component are adopted, and the internal and external common waterproof effect is achieved; the defoaming agent disclosed by the invention has good dispersity and defoaming performance in concrete, and can also fill part of micropores of the concrete to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials, and in particular relates to a high-strength waterproof concrete pole. Background Art

[0002] Concrete poles are a widely used pole tower structure in the field of overhead lines in our country. Since ordinary concrete poles have weaknesses such as low bending strength and heavy weight, the service life of the poles is not long and the maintenance workload is large. Generally, concrete poles are made of prestressed steel bars and concrete as the main materials, using the pre-tensioning prestressed centrifugal forming process and steam curing to form a prefabricated concrete component. High-strength concrete is a new type of cement-based material with excellent mechanical properties and can be used in concrete pole structures.

[0003] However, one of the main challenges faced by concrete poles in actual use is the corrosion problem caused by water intrusion, especially in harsh environmental conditions, such as high humidity areas, acid rain-prone areas, salt spray environments, or areas with frequent freeze-thaw cycles. According to the "2021 Guangdong Province Ecological Environment Bulletin", in terms of urban precipitation in Guangdong Province, the average pH value of precipitation in Guangdong Province is 5.72, and the average pH range is between 5.13 (Jiangmen) and 7.04 (Shanwei); the frequency of acid rain is 10.7%; acid rain occurs in 15 cities (pH minimum value <5.6), and 4 cities are polluted by acid rain (pH average <5.6). In addition to rainwater, when concrete poles are used in low-lying areas, there is often water accumulation in the buried section of the pole body, and the moisture around the pole body will also penetrate into the concrete pores on the inner wall of the pole, thereby greatly shortening the service life of the high-voltage pole.

[0004] In various harsh environments, concrete poles are subjected to the effects of corrosive media for a long time, which leads to cracking of concrete structure performance and reduced durability, thus affecting local power transmission projects. At present, the main methods for waterproofing concrete poles are: 1) The initial waterproofing measures mainly rely on the density of the concrete itself,

[0005] 1) Reduce porosity by optimizing the mixing ratio and increasing the strength grade of cement 2) External coating technology: such as asphalt, polyurethane, epoxy resin and other materials. These coatings improve the waterproof performance of poles to a certain extent, but there are problems such as coating aging, peeling, and potential harm to the environment; 3) With the development of materials science, waterproofing agents (such as silane, silanol, polymers, etc.) have begun to be added to concrete, which significantly improves the impermeability of concrete. This type of waterproofing agent can not only fill the micropores inside the concrete, but also enhance the corrosion resistance of the concrete to a certain extent. Summary of the invention

[0006] The present invention provides a high-strength waterproof concrete pole, which adopts a waterproof coating and a defoamer with a multi-arm star polymer as a main component to achieve the function of waterproofing both inside and outside; the defoamer of the present invention has good dispersibility and defoaming performance in concrete, and can also fill part of the micropores of the concrete to a certain extent.

[0007] The technical solution for achieving the purpose of the present invention is as follows:

[0008] A high-strength waterproof concrete pole, comprising high-strength waterproof concrete, a steel skeleton and a waterproof coating applied on the surface of the pole, wherein the high-strength waterproof concrete comprises 750-850 kg / m of cement in terms of mix ratio. 3 Silica fume 130~170kg / m 3 , Sand 1000~1300kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 10~15kg / m 3 , Water 170~190kg / m 3 and defoamer 0.5~1.5kg / m 3 ;

[0009] The defoamer comprises, by weight, 40 to 50 parts of a multi-arm star polymer, 1 to 2 parts of an emulsifier and 40 to 50 parts of water;

[0010] The multi-arm star polymer is composed of one initiator molecule and 3 to 8 linear polymer chains;

[0011] The initiating molecule is one or more of a polyamino compound and a polyhydroxy compound modified by a halogenated acyl halide compound;

[0012] The linear polymer chain has the following molecular structure:

[0013] Wherein R is the initiating molecule connected to the linear polymer chain; wherein R1, R2 and R3 are at least one of methyl and hydrogen, and wherein a:b:c=(80-90):(5-10):(5-10).

[0014] Preferably, the auxiliary emulsifier is selected from at least one of polyoxyethylene ethers and polysorbates.

[0015] Preferably, the initiating molecule is one or more of glycerol, trimethylolpropane, 1,3,5-triazine-2,4,6-triamine, 1,3,5,7-tetrahydroxyadamantane, dipentaerythritol and hexamethylol melamine modified with halogenated acyl halide compounds.

[0016] More preferably, the initiator molecule has the following molecular structure:

[0017]

[0018] Specifically, the preparation method of the multi-arm star polymer is as follows:

[0019] S1. Take a dry reaction kettle, add initiator molecules, cuprous bromide, hydrogen-containing acrylic siloxane monomers, add solvent, freeze-thaw degassing three times, then add ligand N,N,N',N,'N"-pentamethyldiethylenetriamine dispersed in anisole under nitrogen or argon purge, react at a temperature of 50-60°C for 2-3h, after the reaction is completed, introduce oxygen in an ice water bath to stop the reaction, pass the mixture product through a silica gel column to remove the catalyst, and precipitate the filtrate in a mixed solution of methanol and water to obtain a multi-arm star polymer precursor;

[0020] S2. Take a dry reaction kettle, add a multi-arm star polymer precursor, allyl trimethylammonium chloride and allyl glycidyl ether and dissolve them in a dry toluene solvent. Degas the mixture three times by freeze-thawing. Then, add a Custer catalyst under nitrogen or argon purge. Stir the reaction at a temperature of 55-65°C for 2-3 hours. Pass the mixture product through a silica gel column to remove the catalyst, and remove the solvent to obtain a multi-arm star polymer.

[0021] Preferably, the molar ratio of the initiating molecule: hydrogen-containing acrylate siloxane monomer: cuprous bromide: ligand N,N,N',N,'N"-pentamethyldiethylenetriamineanisole in step S1 is 1:(400-600):(4-10):(8-20); and the amount of Custer catalyst added in step S2 is 0.1-0.3% of the total amount of allyltrimethylammonium chloride and allyl glycidyl ether.

[0022] Preferably, the preparation method of the defoamer is as follows:

[0023] 1) After mixing the multi-arm star polymer and the auxiliary emulsifier, heating to a temperature of 60-80° C., stirring at a speed of 300-400 rpm for 10-15 minutes to obtain an oil phase;

[0024] 2) Deionized water is heated to a temperature of 60-80° C. The oil phase obtained in step 1) is slowly added to the water phase, stirred at a speed of 1500-2000 rpm for 25-35 min, the pH is controlled to be 6.0-7.5, and the defoaming agent is obtained after cooling to room temperature.

[0025] The present invention also discloses a method for preparing a high-strength waterproof concrete pole, comprising the following steps:

[0026] Mix cement, silica fume and sand according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, then add water reducer, continue stirring for 2 to 10 minutes, then slowly add steel fiber and defoaming agent, continue stirring for 2 to 10 minutes, unload the material, put the steel skeleton into the mold and cast it, produce it by centrifugal molding process, cure it by normal pressure steam curing, demould the pole after curing, and spray silicon-based reactive waterproof coating on the surface of the pole.

[0027] It should be noted that the defoaming component in the defoamer of the present invention is a multi-arm star polymer containing a cationic quaternary ammonium salt structure, while the cement surface is positively charged and the water reducer is negatively charged. Therefore, in use, the water reducer must be added first so that the water reducer can be fully adsorbed on the cement surface through electrostatic attraction to avoid mutual influence between the cationic quaternary ammonium salt structure and the water reducer.

[0028] Beneficial Effects

[0029] The present invention has the following beneficial effects: a waterproof coating and a defoamer with a multi-arm star polymer as the main component are used to play the role of waterproofing both inside and outside, and a high-strength waterproof concrete pole is prepared. The defoamer with a multi-arm star polymer as the main component has the following advantages: 1) the star-shaped topological structure makes the molecule have a multi-arm feature, which increases the contact area between the molecule and the bubble; the star-shaped structure has a lower viscosity than the linear structure, which is conducive to dispersion and migration; the multi-arm structure provides more functional group contact points, which improves the defoaming efficiency; 2) it contains a large number of Si-H structures, and the Si-H structure has a lower surface energy. When the defoamer molecules migrate to the bubble surface, the Si-H groups will be preferentially arranged at the gas / liquid interface, which reduces the surface tension of the liquid and enhances the defoaming effect; 3) the epoxy group of the outer arm, the cationic quaternary ammonium salt structure and the polar structure of the main chain help the defoamer to disperse in the concrete and enhance the compatibility; 4) the epoxy group of the outer arm can be combined with the cement molecule through chemical bonding in the later stage, filling part of the micropores of the concrete to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The diagram is a synthetic route and structural schematic diagram of the multi-arm star polymer of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0033] The raw materials and equipment used in the embodiments and comparative examples are described as follows:

[0034] Cement: Portland cement, PII 52.5R, produced by Zhujiang Cement Plant;

[0035] Silica fume: semi-densified silica fume, SiO2 content 96%, purchased from Sichuan Ewende, 960U;

[0036] Sand: Qingyuan river sand, fineness modulus 2.0-3.0;

[0037] Steel fiber: end hook type steel fiber, SF100 / 60BP, purchased from Bolpais;

[0038] Water reducing agent: polycarboxylic acid water reducing agent, Purchased from Jiangsu Subot;

[0039] Water: Guangzhou tap water, in compliance with the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006);

[0040] Prestressed longitudinal force steel wire: diameter 12 mm, grade SWRH72B, purchased from Shagang Steel;

[0041] Longitudinal stress-bearing steel bars: diameter 28 mm, grade HRB500E, purchased from Shagang Steel;

[0042] Spiral ribs: 5 mm in diameter, grade DC01 purchased from Shagang Steel;

[0043] Cold drawn low carbon steel wire: 8 mm in diameter, grade DC01, purchased from Shagang Steel.

[0044] Tween 60: purchased from Aiko Reagents;

[0045] Span 60: purchased from Aike Reagents;

[0046] Cuprous bromide: 99.9%, purchased from Shanghai Aladdin;

[0047] 2-Bromoisobutyryl bromide: purchased from Shanghai Aladdin;

[0048] Dipentaerythritol: purchased from Shanghai Aladdin;

[0049] N,N,N',N,'N"-pentamethyldiethylenetriamine: purchased from Shanghai Aladdin;

[0050] Hydroxyethyl methacrylate: purchased from Shanghai Aladdin;

[0051] Custer catalyst: Pt content 2%, purchased from Shanghai MacLean Biochemical Technology;

[0052] Hexamethylcyclotrisiloxane: purchased from Shanghai Aladdin;

[0053] Dimethyl monochlorosilane: purchased from Shanghai Aladdin;

[0054] Allyltrimethylammonium chloride: purchased from Shanghai BiDe;

[0055] Allyl glycidyl ether: purchased from Aiko Reagents;

[0056] Methyl 2-bromoisobutyrate: purchased from Shanghai Aladdin;

[0057] Silicon-based reactive waterproof coating: Beixin waterproof α-silane modified polymer waterproof coating RAC-101 exposed type.

[0058] Triggering molecules (homemade)

[0059] It is obtained by acylation reaction of dipentaerythritol and 2-bromoisobutyryl bromide, which is a conventional preparation method in the art.

[0060] Hydrogenated acrylate siloxane monomer

[0061] Under argon environment, 1 mol of hexamethylcyclotrisiloxane was placed in a round-bottom flask, 1 mol of dimethylchlorosilane and 50 ml of acetonitrile were added, and then a catalytic amount of dimethylformamide was added. After the mixture was stirred at room temperature for 65 h, the reaction mixture was directly purified by vacuum distillation, and the fractions at 39-41 °C were collected at 1.2 mbar.

[0062] Under a nitrogen atmosphere, at a temperature of 0°C, 2.5 mol of hydroxyethyl methacrylate and 3.0 mol of pyridine were dissolved in dry toluene and added to a reactor. The 1 mol fraction obtained above was dissolved in dry toluene and slowly added dropwise to the reactor. The mixture was stirred for 30 min, heated to 50°C and stirred for 12 h. After completion, the toluene was washed with deionized water, the organic phase was collected, the solvent was removed, and the mixture was purified by column chromatography to obtain a hydrogenated acrylate siloxane monomer.

[0063] Multi-arm star polymer 1

[0064] S1. Take a dry reactor, add 0.0025 mol initiator molecule, 0.01 mol cuprous bromide, 1 mol hydrogenated acrylate siloxane monomer, freeze-thaw degassing three times, then add anisole solution containing 0.02 mol of ligand N,N,N',N,'N"-pentamethyldiethylenetriamine under nitrogen purge, react at 55°C for 2h, after the reaction is completed, introduce oxygen in an ice-water bath to stop the reaction, pass the mixture product through a silica gel column to remove the catalyst, and precipitate the filtrate in a mixed solution of methanol and water to obtain a multi-arm star polymer precursor;

[0065] S2. Take a dry reactor, add the above-obtained multi-arm star polymer precursor, 0.056 mol of allyl trimethyl ammonium chloride and 0.056 mol of allyl glycidyl ether dissolved in dry toluene solvent, freeze-thaw degassing three times, then add 1 drop of Custer catalyst under nitrogen purge, stir and react at 60°C for 3 hours, pass the mixture product through a silica gel column to remove the catalyst, remove the solvent to obtain a multi-arm star polymer. (i.e. attached Figure 1 For the middle molecule, the reaction is carried out according to the proportion of a (90%), b (5%) and c (5%).

[0066] Multi-arm star polymer 2

[0067] S1. Take a dry reactor, add 0.00167 mol initiator molecule, 0.0167 mol cuprous bromide, 1 mol hydrogenated acrylate siloxane monomer, freeze-thaw degassing three times, then add anisole solution containing 0.0334 mol of ligand N,N,N',N,'N"-pentamethyldiethylenetriamine under nitrogen purge, react at 55°C for 2h, after the reaction is completed, introduce oxygen in an ice-water bath to stop the reaction, pass the mixture product through a silica gel column to remove the catalyst, and precipitate the filtrate in a mixed solution of methanol and water to obtain a multi-arm star polymer precursor;

[0068] S2. Take a dry reactor, add the above-obtained multi-arm star polymer precursor, 0.125 mol of allyl trimethyl ammonium chloride and 0.125 mol of allyl glycidyl ether dissolved in dry toluene solvent, freeze-thaw degassing three times, then add 2 drops of Custer catalyst under nitrogen purge, stir and react at 60°C for 3 hours, pass the mixture product through a silica gel column to remove the catalyst, remove the solvent to obtain a multi-arm star polymer. (i.e. attached Figure 1 For the middle molecule, a accounts for 80%, b accounts for 10%, and c accounts for 10%)

[0069] Multi-arm star polymer 3

[0070] S1. Take a dry reactor, add 0.002 mol initiator molecule, 0.02 mol cuprous bromide, 1 mol hydrogenated acrylate siloxane monomer, freeze-thaw degassing three times, then add anisole solution containing 0.04 mol ligand N,N,N',N,'N"-pentamethyldiethylenetriamine under argon purge, react at 55°C for 2h, after the reaction is completed, introduce oxygen in an ice-water bath to stop the reaction, pass the mixture product through a silica gel column to remove the catalyst, and precipitate the filtrate in a mixed solution of methanol and water to obtain a multi-arm star polymer precursor;

[0071] S2. Take a dry reactor, add the above-obtained multi-arm star polymer precursor, 0.095 mol of allyl trimethyl ammonium chloride and 0.095 mol of allyl glycidyl ether dissolved in dry toluene solvent, freeze-thaw degassing three times, then add 2 drops of Custer catalyst under nitrogen purge, stir and react at 60°C for 3 hours, pass the mixture product through a silica gel column to remove the catalyst, remove the solvent to obtain a multi-arm star polymer. (i.e. attached Figure 1 For the middle molecule, a accounts for 84%, b accounts for 8%, and c accounts for 8%)

[0072] Multi-arm star polymer 4

[0073] Compared with the preparation method of multi-arm star polymer 3, the difference is that only step S1 is performed. Figure 1 Middle molecule, a = 100%, b = 0%, c = 0%)

[0074] Multi-arm star polymer 5

[0075] Compared with the preparation method of multi-arm star polymer 3, the difference is that in step S2, 0.095 mol of allyl trimethyl ammonium chloride is replaced by 0.533 mol of allyl trimethyl ammonium chloride, and 0.095 mol of allyl glycidyl ether is replaced by 0.133 mol of allyl glycidyl ether. Figure 1 For the middle molecule, a accounts for 60%, b accounts for 8%, and c accounts for 32%

[0076] Multi-arm star polymer 6

[0077] Compared with the preparation method of multi-arm star polymer 3, the difference is that in step S2, 0.095 mol of allyl trimethyl ammonium chloride is replaced by 0.133 mol of allyl trimethyl ammonium chloride, and 0.095 mol of allyl glycidyl ether is replaced by 0.533 mol of allyl glycidyl ether. Figure 1 For the middle molecule, a accounts for 60%, b accounts for 32%, and c accounts for 8%)

[0078] Linear polymers

[0079] Compared with the preparation method of the multi-arm star polymer 3, the difference is that 0.002 mol of the initiator molecule is replaced by methyl 2-bromoisobutyrate.

[0080] Unless otherwise specified, the components and raw materials used in the preparation examples, embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0081] The following is the test method of the performance parameters involved in the present invention:

[0082] (1) Absolute molecular weight Mw : Determined by static light scattering technique of GPC-MALLS system;

[0083] (2) Polymer dispersibility index (PDI): measured by GPC instrument with differential detector;

[0084] (3) Surface tension: measured in accordance with GB / T 8077-2023 Test method for homogeneity of concrete admixtures;

[0085] (4) Air content: measured according to GB / T50080-2016 "Standard for test methods of performance of ordinary concrete mixtures";

[0086] (5) Anti-seepage performance: The anti-seepage performance of concrete specimens was tested using the water seepage height method in accordance with GB / T 50082-2009 “Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete”;

[0087] (6) Compressive strength: The specimen size is 150 mm × 150 mm × 150 mm, and the test is carried out in accordance with the relevant provisions of GB / T50081-2019.

[0088] (7) Workability: According to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the slump test, Vebe consistency test, and cohesiveness and water retention test are performed.

[0089] Preparation of Defoamers 1 to 7

[0090] 1) The multi-arm star polymers 1 to 6 and the linear polymer are sequentially mixed with the co-emulsifier, heated to 80° C., and stirred at 400 rpm for 15 min;

[0091] 2) Deionized water was heated to 80° C. The oil phase obtained in step 1) was slowly added to the aqueous phase, stirred at 2000 rpm for 35 min, the pH was controlled to be 6.5, and the defoaming agent was obtained after cooling to room temperature.

[0092] Table 1 Characterization of polymers and surface tension of the corresponding defoamers prepared

[0093] M PDI Defoamer surface tension (mN / m) Multi-arm star polymer 1 162200 1.12 23.01 Multi-arm star polymer 2 243800 1.28 23.53 Multi-arm star polymer 3 212000 1.18 23.24 Multi-arm star polymer 4 216100 1.16 21.19 Multi-arm star polymer 5 225100 1.20 28.51 Multi-arm star polymer 6 206800 1.21 26.64 Linear polymers 183600 1.12 24.69

[0094] From the data of multi-arm star polymers 3 to 6 in Table 1, it can be seen that the higher the ratio of quaternary ammonium salt and epoxy group, the greater the surface tension of the corresponding defoamer; from the data of multi-arm star polymer 3 and linear polymer, it can be seen that the surface tension of the defoamer corresponding to the multi-arm star polymer is smaller.

[0095] Steel skeleton:

[0096] Six prestressed longitudinal force-bearing steel wires are used, and eight longitudinal force-bearing steel bars are used as the main reinforcement; cold-drawn low-carbon steel wires are used as the frame rings with a spacing of 600mm; spiral reinforcements are used as annular structures, with a spacing of 50mm within 1.5m from both ends of the pole, and a spacing of 100mm in the remaining sections.

[0097] A method for preparing a high-strength waterproof concrete pole comprises the following steps:

[0098] Cement, silica fume and sand were mixed according to the mix ratio, stirred for 3 minutes, water was added, and water reducer was added after stirring for 3 minutes. After stirring for 8 minutes, steel fiber and defoaming agent were slowly added, and stirring was continued for 8 minutes. The material was discharged. According to the relevant provisions of "Ring Concrete Poles" GB4623-2014, the same steel skeleton was used, and the C120 high-performance green concrete pole with a designed cracking test bending moment of 97.5 kN·m was used. The wall thickness was 50 mm, the shape was a tapered pole with a taper of 1 / 75, a tip diameter of 190 mm, a root diameter of 350 mm, and a pole length of 12 m. It was produced by centrifugal molding process and cured by normal pressure steam curing for 27 days. The pole was demoulded after curing, and a silicon-based reactive waterproof coating was sprayed on the surface of the pole.

[0099] Table 2 Examples 1 to 11, high strength waterproof concrete formula (kg / m 3 )

[0100] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 cement 750 850 820 820 820 820 820 820 Silica Fume 130 170 149 149 149 149 149 149 Sand 1300 1000 1241 1241 1241 1241 1241 1241 Steel Fiber 150 250 231 231 231 231 231 231 Water reducing agent 10 15 12 12 12 12 12 12 water 170 190 180 180 180 180 180 180 Defoamer 1 0.5 1.5 1.3 Defoamer 2 1.3 Defoamer 3 1.3 0.5 1.0 1.5

[0101] Table 3 Comparative Examples 1 to 6, high strength waterproof concrete formula (kg / m 3 )

[0102] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 cement 820 820 820 820 820 820 Silica Fume 149 149 149 149 149 149 Sand 1241 1241 1241 1241 1241 1241 Steel Fiber 231 231 231 231 231 231 Water reducing agent 12 12 12 12 12 12 water 180 180 180 180 180 180 Defoamer 3 2.5 Defoamer 4 1.3 Defoamer 5 1.3 Defoamer 6 1.3 Defoamer 7 1.3

[0103] Table 4 High strength waterproof concrete performance test

[0104]

[0105]

[0106] It can be seen from the data of Examples 1 to 8 and Comparative Examples 1 to 6 in Table 4 that adding an appropriate amount of the defoamer prepared by the present invention can make the concrete have better compressive strength, lower air content and better impermeability. It can be seen from the data of Examples 4, 6, 7 and 8 that within a certain range, as the amount of defoamer increases, the performance of the concrete becomes better; it can be seen from the data of Comparative Example 1 that without adding the defoamer of the present invention, the strength and impermeability are both poor; it can be seen from the data of Comparative Example 2 that adding too much defoamer of the present invention will lead to a decrease in performance and poor workability; it can be seen from the data of Comparative Example 3 that although the surface tension of defoamer 4 is low, the air content of the concrete is high, which is due to the poor dispersibility of the defoamer in the concrete; it can be seen from the data of Comparative Example 4 that too much quaternary ammonium salt structure has a negative effect on the defoaming ability of defoamer 5 in concrete. The force is also affected. On the one hand, the Si-H structure is reduced, and on the other hand, there are too many hydrophilic groups, which reduce the rate at which the defoamer migrates to the bubble and water page. From the data of Comparative Example 5, it can be seen that too many epoxy groups in defoamer 6 will also lead to a decrease in concrete performance. This is because the excessive epoxy groups increase the probability of the early epoxy groups reacting with the concrete molecules, making it unable to exert its defoaming ability, but the increase in epoxy groups slightly improves its anti-permeability performance. From the data of Comparative Example 6, it can be seen that the concrete performance is poor when the linear structure defoamer 7 is added, indicating that the defoaming ability, dispersibility and workability of the linear structure are all poor.

[0107] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-strength waterproof concrete pole, characterized in that: It includes high-strength waterproof concrete, a steel skeleton and a waterproof coating applied on the surface of the pole. The high-strength waterproof concrete includes 750-850kg / m of cement in terms of mix ratio. 3 Silica fume 130~170kg / m 3 , Sand 1000~1300kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 10~15kg / m 3 , Water 170~190kg / m 3 and defoamer 0.5~1.5kg / m 3 ; The defoamer, in parts by weight, comprises 40-50 parts of a multi-arm star polymer, 1-2 parts of an emulsifier and 40-50 parts of water; the multi-arm star polymer is composed of 1 initiator molecule and 3-8 linear polymer chains; the initiator molecule is one or more of a polyamino compound modified by a halogenated acyl halide compound and a polyhydroxy compound modified by a halogenated acyl halide compound; The linear polymer chain has the following molecular structure: Wherein R is the initiating molecule to which the linear polymer chain is connected; wherein R1, R2 and R3 are independently represented by one of methyl and hydrogen, wherein a:b:c=(80-90):(5-10):(5-10).

2. A high-strength waterproof concrete pole as claimed in claim 1, characterized in that: The auxiliary emulsifier is selected from at least one of polyoxyethylene ethers and polysorbates.

3. A high-strength waterproof concrete pole as claimed in claim 1, characterized in that: The initiating molecule is one or more of glycerol, trimethylolpropane, 1,3,5-triazine-2,4,6-triamine, 1,3,5,7-tetrahydroxyadamantane, dipentaerythritol and hexamethylol melamine modified by halogenated acyl halide compounds.

4. A high-strength waterproof concrete pole as claimed in claim 1, characterized in that: The preparation method of the multi-arm star polymer is as follows: S1. Take a dry reaction kettle, add initiator molecules, cuprous bromide, hydrogen-containing acrylic siloxane monomers, and solvent, freeze-thaw degassing three times, then add ligand N,N,N',N,'N"-pentamethyldiethylenetriamine dispersed in anisole under nitrogen or argon purge, react at a temperature of 50-60°C for 2-3h, after the reaction is completed, introduce oxygen in an ice water bath to stop the reaction, pass the mixture product through a silica gel column to remove the catalyst, and precipitate the filtrate in a mixed solution of methanol and water to obtain a multi-arm star polymer precursor; S2. Take a dry reaction kettle, add a multi-arm star polymer precursor, allyl trimethylammonium chloride and allyl glycidyl ether and dissolve them in a dry toluene solvent, freeze-thaw and degas three times, then add a Custer catalyst under nitrogen or argon purge, stir and react at a temperature of 55-65°C for 2-3 hours, pass the mixture product through a silica gel column to remove the catalyst, and remove the solvent to obtain a multi-arm star polymer.

5. A high-strength waterproof concrete pole as claimed in claim 4, characterized in that: The molar ratio of the initiating molecule: hydrogen-containing acrylic siloxane monomer: cuprous bromide: ligand N,N,N',N,'N"-pentamethyldiethylenetriamine in step S1 is 1:(400-600):(4-10):(8-20); the amount of the Custer catalyst added in step S2 is 0.1-0.3% of the total amount of allyl trimethyl ammonium chloride and allyl glycidyl ether.

6. A high-strength waterproof concrete pole as claimed in claim 1, characterized in that: The preparation method of the defoamer is as follows: 1) After mixing the multi-arm star polymer and the auxiliary emulsifier, heating to a temperature of 60-80° C., stirring at a speed of 300-400 rpm for 10-15 minutes to obtain an oil phase; 2) Deionized water is heated to a temperature of 60-80° C., the oil phase obtained in step 1) is slowly added into the water, stirred at a speed of 1500-2000 rpm for 25-35 min, the pH is controlled to be 6.0-7.5, and the defoaming agent is obtained after cooling to room temperature.

7. A method for preparing a high-strength waterproof concrete pole according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mix cement, silica fume and sand according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, then add water reducer, continue stirring for 2 to 10 minutes, then slowly add steel fiber and defoaming agent, continue stirring for 2 to 10 minutes, unload the material, put the steel skeleton into the mold and cast it, produce it by centrifugal molding process, cure it by normal pressure steam curing, demould the pole after curing, and spray silicon-based reactive waterproof coating on the surface of the pole.

Citation Information

Patent Citations

  • Steam-curing-free corrosion-resistant concrete pole and preparation method thereof

    CN109252729A

  • Ultra-high strength concrete and thin-wall pole prepared from same

    CN109912272A

  • Star polymer silicone oil, polymer silicone oil, preparation method of star polymer silicone oil and defoaming agent prepared from star polymer silicone oil

    CN118834392A

Cited By

  • High-strength annular prestressed concrete pole and preparation method thereof

    CN121044855A

  • Anti-crack concrete pole material and preparation method thereof

    CN122059661A

  • Anti-crack concrete pole material and preparation method thereof

    CN122059661B